Analytical method development and validation for simultaneous estimation of Teneligliptin hydrobromide hydrate and Metformin hydrochloride from it’s pharmaceutical dosage form by three different UV spectrophotometric methods - Ashim Kumar Sen, Denish N. Hinsu, Dhanya B. Sen, Aarti S. Zanwar, Rajesh A. Maheshwari, Vikas R. Chandrakar (Journal of Applied Pharmaceutical Science, 2016)
Three new UV spectrophotometric methods namely simultaneous equation, absorbance ratio and first derivative (zero crossing) spectroscopic methods were developed and validated for simultaneous estimation of teneligliptin hydrobromide hydrate and metformin hydrochloride in tablet formulation which were simple, sensitive, precise and accurate. In simultaneous equation method, absorbance was measured at 237 and 246 nm for both the drugs. Teneligliptin hydrobromide hydrate and metformin hydrochloride was estimated using 237 and 247.5 nm in absorbance ratio method. First derivative (zero crossing) method was based on the transformation of UV spectra in to first derivative spectra followed by measurement of first derivative signal at 237 and 246 nm for teneligliptin hydrobromide hydrate and metformin hydrochloride, respectively using 2 nm as wavelength interval (Δλ) and 1 as scaling factor. Developed methods were validated according to ICH guidelines including parameters viz., specificity, linearity and range, precision, accuracy, limit of detection and quantification. All the three methods showed linear response in the concentration range of 1-20 µg/ml for both the drugs. Results of method validation parameters follows ICH guideline acceptable limits. Based on the assay results obtained, methods were compared using one-way ANOVA followed by Bonferroni multiple comparison tests (95% confidence level) using computer based fitting program (Prism, Graphpad version 5, Graphpad Software Inc). Outcome of the statistical analysis proved that there was no considerable dissimilarity between all the developed methods. Methods were found to be simple, fast, highly sensitive, cost effective and hence can be useful for simultaneous estimation of teneligliptin hydrobromide hydrate and metformin hydrochloride in commercial tablet formulation for routine quality control analysis.
Keywords: Teneligliptin hydrobromide hydrate, metformin hydrochloride, simultaneous equation, absorbance ratio, first derivative (zero crossing) spectroscopic methods, tablet formulation.